Assessing GFDL‐ESM4.1 Climate Responses to a Stratospheric Aerosol Injection Strategy Intended to Avoid Overshoot 2.0°C Warming - Zhang, Shipeng; Naik, Vaishali; Paynter, David; Tilmes, Simone; John, Jasmin (Geophysical research letters, 2024)
In this work, we apply the GFDL Earth System Model (GFDL‐ESM4.1) to explore the climate responses to a stratospheric aerosol injection (SAI) scenario that aims to restrict global warming to 2.0°C above pre‐industrial levels (1850–1900) under the CMIP6 overshoot scenario (SSP5‐34‐OS). Simulations of this SAI scenario with the CESM Whole Atmosphere Community Climate Model (CESM2‐WACCM6) showed nearly unchanged interhemispheric and pole‐to‐Equator surface temperature gradients relative to present‐day conditions around 2020, and reduced global impacts, such as heatwaves, sea ice melting, and shifting precipitation patterns (Tilmes et al., 2020, https://doi.org/10.5194/esd‐11‐579‐2020). However, model structural uncertainties can lead to varying climate projections under the same forcing. Implementing identical stratospheric aerosol radiative properties in GFDL‐ESM4.1, which has a much lower Effective Climate Sensitivity compared to CESM2‐WACCM6, resulted in a decrease in global‐mean surface temperature by more than 1.5°C and a corresponding reduction in precipitation responses. Two major reasons contribute to the different temperature response between the two models: first, GFDL‐ESM4.1 has less warming in the SSP534‐OS scenario; second, GFDL‐ESM4.1 has shown more pronounced cooling in response to the same stratospheric AOD perturbation. Notably, the Southern Hemisphere experiences substantial cooling compared to the Northern Hemisphere, accompanied by a northward shift of the Intertropical Convergence Zone (ITCZ). Furthermore, our analysis reveals that spatially heterogeneous forcing within the SAI scenario results in diverse climate feedback parameters in the GFDL‐ESM4.1 model, through varying surface warming/cooling patterns. This research highlights the importance of considering model structural uncertainties and forcing spatial patterns for a comprehensive evaluation of future scenarios and geoengineering strategies. Plain Language Summary Solar radiation modification (SRM) has been explored as a way to mitigate global warming due to ongoing greenhouse gas emissions, but the full consequences remain highly uncertain. One SRM approach, which involves injecting small scattering particles into the upper atmosphere to reduce incoming sunlight, was previously tested using the CESM2‐WACCM6 climate model to limit global warming to 2.0°C above the pre‐industrial level. Applying the stratospheric aerosol radiative properties in the GFDL‐ESM4.1 model, we found a more than 1.5°C decrease in Earth's surface temperature and a reduction in rainfall, compared to CESM2‐WACCM6. In particular, the Southern Hemisphere experienced greater cooling compared to the Northern Hemisphere, leading to a northward shift in the tropical rainfall zone. Our findings also showed that spatially uneven particle injection results in varied climate responses within the same model. These results underscore the importance of considering the different characteristics of climate models and the spatial patterns of implementation when evaluating the potential impacts of SRM strategies. Key Points The stratospheric aerosol injection (SAI) strategy used in CESM2‐WACCM6 to target a warming of 2.0°C leads to a global surface overcooling in GFDL‐ESM4.1 The SAI applied on the SSP5‐34‐OS scenario also results in a decrease in global precipitation and a northward shift of ITCZ in GFDL‐ESM4.1 Strong spatially heterogeneous forcing leads to varying climate feedback parameters within the GFDL‐ESM4.1